The River War : An Account of the Reconquest of the Sudan - Churchill, Winston S., 1874-1965 (London Eyre & Spottiswoode, 1951)
Packed in its dense, historic city centers, Italy holds some of the most prized architecture and art in the world, with which planners and politicians have had to negotiate as they struggle to cope with massive migration from the countryside to the city. Early modern architecture coincided with a sustained drive to transform a country that was still primarily rural into a modern industrial state, and throughout the twentieth century, architects in Italy have attempted to define the role of architecture within a capitalist economy and under diverse political systems. In Italy: Modern Architectures in History, Diane Yvonne Ghirardo addresses these and other issues in her analysis of the last century of Italy$1 (Bs building practices.s
Include Maps, Appendix and Index
Keywords: Sudan--Khartoum -- Great Britain Army -- British Colonies